2020
DOI: 10.1186/s13643-020-01433-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin D supplementation on fasting glucose, dyslipidemia, blood pressure, and abdominal obesity among patients with metabolic syndrome: a protocol for systematic review and meta-analysis of randomized controlled trials

Abstract: Background Vitamin D deficiency can play a role in extraskeletal functions that are involved with a set of risk factors associated with metabolic syndrome (MetS). The purpose of this review is to investigate the impact of vitamin D supplementation on fasting glucose, dyslipidemia, blood pressure, and abdominal obesity among patients with MetS. Methods EMBASE, Medline, Web of Science, Lilacs, the Cochrane Central Register of Controlled Trials, clinicaltrials.gov database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Accordingly, correcting vitamin D deficiency through VDS was suggested to alleviate MetS, specifically the atherogenic dyslipidemia component of this syndrome [11]. This topic is gaining attention in the research world and is of clinical relevance [41].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, correcting vitamin D deficiency through VDS was suggested to alleviate MetS, specifically the atherogenic dyslipidemia component of this syndrome [11]. This topic is gaining attention in the research world and is of clinical relevance [41].…”
Section: Discussionmentioning
confidence: 99%
“…A recently developed analytical tool, TBS, has rarely been used in the assessment and management of the impact of serum 25(OH)D levels on bone microarchitecture. In studies of adult individuals, the preservation of bone mass and microarchitecture at the spine has been reported with combined calcium and vitamin D supplementation [19]; however, correction of vitamin D insufficiency (reference range, ≥30 ng/mL) in postmenopausal women showed no clinically meaningful beneficial effects on BMD [20]. One study reported that TBS did not differ by vitamin D level in patients with primary hyperparathyroidism (reference range, 14 to 65 pg/ml) [21].…”
Section: Bmi and The Relationship Between Serum 25(oh)d Level And Tbsmentioning
confidence: 99%
“…The VDI is associated with several components of MetS [10]. The inverse correlation between Vitamin D concentration and the development of MetS could be explained by the dependence of insulin production in pancreatic β cells on Vitamin D and its receptor interaction [11], obesity resulting in more sequestration of vitamin D in adipose tissue, and greater volumetric dilution of serum 25(OH)D level, less sun exposure, poor dietary habits, and varied genetic expression of enzymes involving vitamin D metabolism [17,42].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D levels are also in uenced by age, sex, smoking, sedentary lifestyle, poor dietary habits, sun exposure, sun-protective behavior, latitude of residence, differences in gene expression of vitamin D-metabolizing enzymes, and impaired hepatic 25-hydroxylation [5][6][7][8]. Decreased 25(OH)D levels are closely associated with a variety of illnesses including bone metabolic disorders, tumors, cardiovascular diseases, diabetes mellitus, arterial hypertension, heart failure, peripheral arterial disease, acute myocardial infarction, various types of cancers, autoimmune and in ammatory diseases, decreased immune defenses and increased mortality [9,10]. The vitamin D receptor was found in β cells in the pancreas, adipose, and musculoskeletal tissues and vitamin D inadequacy could compromise the capacity of β cells to convert pro-insulin into insulin [4].…”
Section: Introductionmentioning
confidence: 99%